Leading from the front: exploring the professional and personal nature of research leadership - Damonse, Beverley; Nkomo, Mokubung (South African Journal of Higher Education, 2016)
Research is a key indicator of university performance and research leadership is a critical variable in achieving research excellence. This qualitative research study examined the ‘research stories’ of ten research performing academics and the reported research and mentoring experiences of a sample of 30 of their postgraduate mentees to gain a more nuanced understanding of the nature of research leadership, with special attention to how this influences research performance. The unit of analysis was leadership at the disciplinary level within South African higher education. This article discusses one of the salient features common to the research trajectories in this study, namely, leadership by example of personal scholarship. Academic role models, who are themselves performing scientists and scholars, are essential in influencing the intellectual development of the next generation of researchers